2014
DOI: 10.4236/jwarp.2014.64035
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Surface Water Velocity on Hyporheic Interchange

Abstract: When evaluating hyporheic exchange in a flowing stream, it is inappropriate to directly compare stream stage with subsurface hydraulic head (h) to determine direction and magnitude of the gradient between the stream and the subsurface. In the case of moving water, it is invalid to ignore velocity and to assume that stage equals the net downward pressure on the streambed. The Bernoulli equation describes the distribution of energy within flowing fluids and implies that net pressure decreases as a function of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…While the magnitude varied, the hydraulic gradient indicated that groundwater flowed towards LKC, which was consistent with previous studies reporting LKC as a gaining stream [25,[55][56][57][58]. Evidence of the upwelling of groundwater was observed in several instances while collecting water samples.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…While the magnitude varied, the hydraulic gradient indicated that groundwater flowed towards LKC, which was consistent with previous studies reporting LKC as a gaining stream [25,[55][56][57][58]. Evidence of the upwelling of groundwater was observed in several instances while collecting water samples.…”
Section: Discussionsupporting
confidence: 89%
“…Regardless of whether a stream is gaining or losing water, downwelling into the streambed has been reported [77] and the mixing model quantified the mixing that has occurred (Figure 3d). Stream velocity and gradient influence the rate of downwelling [44,58,77]. At baseflow, when the stream stage is lower and the stream velocity is slower, downwelling stream water will compete against upwelling groundwater.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Hyporheic Zone DOI: http://dx.doi.org /10.5772/intechopen.85218 potentially giving rise to a local reversal in the hydraulic gradient and influx of deeper groundwater [58], despite the higher river stage. Understanding exchanges of this type is particularly important in the characterisation of the hyporheic zone for the management of flood risk.…”
Section: Hydrological Characterisationmentioning
confidence: 99%